Communication Systems Research At Bruceton Safety Research Mine - Howard E. Parkinson (The National Institute for Occupational Safety and Health (NIOSH))
An environment monitoring and communication system has been installed in the Bruceton Mine, and research is under way to improve mine safety. Standard day-to-day mine communications are available, along with additional systems installed to permit experimentation with wireless radio, through-the-earth phones, along-the-roof paging, and mine face machinery communications. Research is continuing and the essential concepts for a dependable whole mine communication system, providing simple environment monitoring, improved day-to-day communications and post-disaster communications, will be demonstrated in a larger mine with about 900 feet of overburden.